Answer:
y = -
x +
![(8)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/yn4wevyeyko2suwcfgivygmyfocr3tiytn.png)
Explanation:
the perpendicular bisector of AB passes through the midpoint of AB at right angles.
find the midpoint using the midpoint formula
with A (- 2, 0 ) and B (0, 6 )
midpoint = (
,
) = (
,
) = (- 1, 3 )
find the gradient m of AB using the gradient formula
m =
![(y_(2)-y_(1) )/(x_(2)-x_(1) )](https://img.qammunity.org/2023/formulas/mathematics/college/jkzrkt8zi557egkc0ias6wietjfal5swo6.png)
with (x₁, y₁ ) = A (- 2, 0 ) and (x₂, y₂ ) = B (0, 6 )
m =
=
=
= 3
given a line with gradient m then the gradient of a line perpendicular to it is
= -
= -
![(1)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/rshimc01547v0bylxspiig5y5rp1hyhlbx.png)
the equation of a line in gradient- slope form is
y = mx + c ( m is the gradient and c the y- intercept )
here m = -
, then
y = -
x + c ← is the partial equation
to find c substitute (- 1, 3 ) into the partial equation
3 =
+ c ⇒ c = 3 -
=
![(8)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/yn4wevyeyko2suwcfgivygmyfocr3tiytn.png)
y = -
x +
← equation of perpendicular bisector